I diritti umani, questi (s)conosciuti (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. Nominare i diritti umani - 3. La questione del fondamento - 4. Rileggendo Bobbio - 5. Considerazioni conclusive.Human Rights, these (un)knownABSTRACT: This paper intends to relaunch the Italian legal and philosophical debate on human rights by taking inspiration from the issue of migrants. The author proposes to reconsider the question of the theoretical foundation as crucial for the future development of the theory and practice of human rights.